The Use of Social Media as a Means of Tourism Promotion City of Pagar Alam (Case Study on Instagram Account @greenparadise_pga16) - Julianti, Rani; Hamidah, Hamidah; Muslimin, Muslimin (Indonesian Journal Publisher, 2024)
This study aims to determine how managers use social media to market their tours and the benefits and drawbacks of using Instagram. This study employs a qualitative method with a descriptive approach. Interviews, observation, and documentation are the methods used to acquire data. The findings revealed that: (1) Instagram is a highly efficient promotional medium, utilizing elements such as photo titles or captions, hashtags, Instagram stories, reposts, and reels, as well as the AIDA concept (Attention, Interest, Desire, Action) to capture followers' attention. (2) Factors that support using Instagram social media to promote Green Paradise Tourism in Pagar Alam City include marketing that uses photo titles or captions. The restricting elements are content to be posted and promoted and competition from other destinations, particularly those with more active promotional strategies or more appeal.